2020
DOI: 10.1177/0194599820934376
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory and Gustatory Dysfunction as an Early Identifier of COVID‐19 in Adults and Children: An International Multicenter Study

Abstract: Objective To evaluate the prevalence and characteristics of olfactory or gustatory dysfunction in coronavirus disease 2019 (COVID-19) patients. Study Design Multicenter case series. Setting Five tertiary care hospitals (3 in China, 1 in France, 1 in Germany). Subjects and Methods In total, 394 polymerase chain reaction (PCR)–confirmed COVID-19-positive patients were screened, and those with olfactory or gustatory dysfunction were included. Data including demographics, COVID-19 severity, patient outcome, and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
158
4
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(182 citation statements)
references
References 16 publications
4
158
4
16
Order By: Relevance
“…We identified 2 meta-analyses of 24 and 21 studies/case reports respectively that described patients with olfactory/ gustatory dysfunction [69,70]. In addition, we describe 11 studies that evaluated olfactory/gustatory dysfunction in COVID-19 patients (Table 6) [71][72][73][74][75][76][77][78][79][80][81].…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 2 meta-analyses of 24 and 21 studies/case reports respectively that described patients with olfactory/ gustatory dysfunction [69,70]. In addition, we describe 11 studies that evaluated olfactory/gustatory dysfunction in COVID-19 patients (Table 6) [71][72][73][74][75][76][77][78][79][80][81].…”
Section: Search Resultsmentioning
confidence: 99%
“…They found that the use of intranasal or oral steroids enhanced the recovery of COVID-19related olfactory/gustatory dysfunction [70]. We found 11 studies that specifically evaluated gustatory and olfactory functions in patients with COVID-19 infection [71][72][73][74][75][76][77][78][79][80][81]. Majority of patients had olfactory/gustatory dysfunction in addition to other symptoms like fever, cough, sore throat, and headache.…”
Section: Olfactory and Gustatory Dysfunctionmentioning
confidence: 95%
“…The prevalence rates of ageusia and anosmia, ageusia, and anosmia were 8.51%, 11.35%, and 4.96%, respectively, making the overall prevalence rate 24.82% Table 1. Qiu et al multi-centric case series study found that 41% of the COVID-19 patients complained from STA [10]. Speth et al reported that the prevalence rate of olfactory dysfunction was 61.2% [11].…”
Section: Discussionmentioning
confidence: 99%
“…Chemosensory dysfunctions are common problems during the pandemic COVID-19 crisis. Smell and taste Abnormalities (STA) were the rst and the only complaints in 10% of subjects, 19% experienced STA before other classical symptoms like fever and cough, as well as 25% of the children had only STA at the time of the presentation [10]. Therefore, these disorders are indicators of early cases of COVID-19 disease and necessary for screening and infection control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation